Reseña de Barcelona, A. (Ed.) (2000), Metaphor and Metonymy at the Crossroads. A cognitive perspective, New York, Mouton de Gruyter. - González Macías, Miguel Ángel (Pragmalingüística, 2011)
<!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> <![endif]--> Se trata de reseña de Barcelona, A. (Ed.) (2000), Metaphor and Metonymy at the Crossroads. A cognitive perspective, New York, Mouton de Gruyter.